2015
DOI: 10.1016/j.jmoneco.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Innovation, diffusion, and trade: Theory and measurement

Abstract: a b s t r a c tWhat are the sources of economic growth? This paper presents a multicountry growth model of innovation and the adoption of foreign technologies through trade. The costs of both domestic innovation and adopting foreign innovations are estimated using data on innovation, output and trade. A decomposition of the sources of growth shows that technology adoption accounts for about 65% of "embodied" growth in developing countries. Developed countries grow mainly through domestic innovation, which expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 43 publications
1
24
0
1
Order By: Relevance
“…Therefore, innovation and international technology diffusion appear to be important determinants of comparative advantage. Our reduced-form results are consistent with structural models that have studied the role of innovation and technology adoption as sources of productivity growth and comparative advantage, such as Cai et al (2017) and Santacreu (2015). n…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, innovation and international technology diffusion appear to be important determinants of comparative advantage. Our reduced-form results are consistent with structural models that have studied the role of innovation and technology adoption as sources of productivity growth and comparative advantage, such as Cai et al (2017) and Santacreu (2015). n…”
Section: Resultssupporting
confidence: 89%
“…4 Higher-income countries are closer to the technology frontier, and we would expect them to benefit more from domestic innovation than lower-income countries. Indeed, in the data, there is a strong positive correlation between the level of income per capita of countries and their investment in R&D. Lower-income countries that are farther away from the technology frontier, however, benefit more from adoption of foreign innovations, as it has been quantified in Santacreu (2015). We conduct the same regression analysis as before for each group of countries and industries.…”
Section: Quantitative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ekonomik büyümenin kaynaklarının neler olduğu sorusundan hareketle Santacreu (2014) tarafından yapılan çalışmanın amacı yabancı faktörleri (ticaret yoluyla yabancı inovasyonun benimsenmesi) ve yerli faktörleri (yerli inovasyon) dikkate alarak "içselleştirilmiş (embodied)" ekonomik büyümeyi ayrıştırmaya yöneliktir. 1996-2007 dönemine ilişkin 30 ülkenin yer aldığı örneklemdeki ülkeler ortak özelliklerine göre (benzer inovasyon yoğunluğu, yaygın ticaret marjinleri ve verimlilik) 3 gruba ayrılmıştır: yükselen piyasalar, daha az inovasyon yapan OECD ülkeleri ve daha fazla inovasyon yapan OECD ülkeleri.…”
Section: Uluslararası İktisadi Ve İdari İncelemeler Dergisiunclassified
“…Indeed, research has shown that low-frequency fluctuations of trade in varieties can explain differences in aggregate productivity growth across countries (Broda et al 2006;Goldberg et al 2010;Santacreu 2014). One interpretation of these findings is that technology is embedded in new goods created through innovation.…”
Section: Introductionmentioning
confidence: 99%